The Relationship Between Personal-Social Guidance And Moral Behavior Of Pgri Junior High School Students In Palangka Raya - Hetty Susanti; Alfiana Fira Syaharani; Indah Sri Utami (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2021)
The phenomena seen in SMP PGRI Palangka Raya are skipping school, bullying, and lying. These behaviors reflects of moral behavior of students in SMP PGRI Palangka Raya that is still not good. This study aims to determine the relationship between personal-social guidance on the moral behavior of students in SMP PGRI Palangka Raya. The method used in this research was quantitative-non-experimental research. The sampling technique used was saturated samples, where all members of the population become research samples. Data was collected using instruments developed based on theory and grid. The collected data were analyzed using the correlation test and a simple regression test. The results of research and discussion show that: (1) 11 (36.67%) students have high personal-social scores (good), 16 students (53.33%) have moderate personal-social scores, and 3 students (10.0%) have low personal-social scores. (2) 4 students (13.33%) have high moral behavior (good), 21 students (70.0%) have moderate moral behavior, and 5 students (16.67%) have low moral behavior. Thus, it can be concluded that 70% of students have moderate moral behavior. (3) The results of data analysis using the correlation test between independent variables (X) of personal-social guidance to the dependent variable (Y) of moral behavior of students obtained correlation coefficient of r count of 0.813 > of r table of 0.3550 with a level of significance of 0,000 < of 0.5. Based on the results of these calculations, the researcher concludes that there is a significant correlation personal-social guidance and the moral behavior of students in SMP PGRI Palangka Raya